A Proposed Model for Assessing Defendant Competence to Self-Represent - White, Mitzi M. S.; Gutheil, Thomas G. (Journal of the American Academy of Psychiatry and the Law Online, 2016)
The increasing number of criminal defendants who are choosing to self-represent poses special challenges for legal systems with regard to the types of limits that should be placed on a defendant’s basic human right to defend himself without the assistance of counsel. While courts strive to respect the dignity and autonomy of the defendant that are encompassed in this right, they also want to ensure that justice is delivered and the dignity of the courtroom is maintained. The Supreme Court of the United States, in its opinion in Indiana v. Edwards (2008), held that while the right to self-represent recognized in Faretta v. California (1975) remains, states and trial judges can place limits on a defendant’s right to self-representation when a defendant lacks the mental capacities needed to prepare and conduct an adequate defense. Following the court’s lead, we first examine the types and range of tasks that a defendant who chooses to self-represent must perform. Based on this analysis, we propose a five-part model that forensic practitioners can use as a conceptual framework for assessing whether a defendant has deficits that would affect his competence to perform critical self-representation tasks. The five areas that the model recommends practitioners assess are whether a defendant can engage in goal-directed behaviors, has sufficient communication skills, can engage in constructive social intercourse, can control his emotions in an adversarial arena, and has the cognitive abilities needed to argue his case adequately. It is recommended that practitioners use the model in their testimony to provide the trier of fact with a comprehensive report of the areas in which a defendant has deficits that will prevent him from protecting his interests in receiving a fair and equitable trial.